Doping-dependent superconducting properties of two-dimensional metals with different types of interparticle coupling (Review Article) - Loktev, V.M.; Turkowski, V.M. (Физика низких температур, 2004)
The superconducting properties of a two-dimensional metallic system with arbitrary carrier
density and both local and various types of the indirect boson-exchange attractive interaction in
the cases of s- and d-wave pairing are analyzed and reviewed at T = 0. In particular, the possibility
of a crossover from the Bose—Einstein condensation regime to Bardeen—Cooper—Schrieffer-like
superconductivity with growing carrier density and changing coupling in the case of different pairing
channels is discussed. Gaussian fluctuations of the order parameter are taken into account, and
the carrier density dependence of the gap magnitude is studied. The role of the form of the
interparticle attractive interaction in the physical behavior of the system is also considered.